Analysis of Accident and Occupational Diseases with HAZOP Method and The Risk Control of Batik Papringan Workers, Banyumas - Parmasari, Damairia Hayu; Suryanto, Suryanto (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
Occupational Safety and Health (OSH)Ã‚Â is an important aspect to pay attention to in the workplace. This is due to the workplace environment that has potential hazards and risks that can cause work-related accidents and diseases. Accidents and occupational diseases need to be prevented and minimized because they reduce work productivity and harm workers and business owners. The risk of accidents and occupational diseases also exists in the informal batik sector. One of the informal Batik sectors in Banyumas Regency is Batik Papringan. Papringan Batik workers have not implemented the OSH Standard Operational Procedure (SOP). This causes workers to experience health complaints such as coughing, itching, and musculoskeletal conditions. Therefore, it is necessary to analyze occupational accidents and diseases with the Hazard and Operability Study (HAZOP) and its control. The research objective was to determine the hazards and risks of accidents and diseases due to the work of Batik Papringan workers. The method used is the HAZOP method. The results showed that the stooped and static sitting posture, exposure to chemicals from wax smoke and dyes and the absence of 5R (Ringkas, Rapi, Resik, Rawat, Rajin) were hazards that pose extreme risks. Risk control in the form of ergonomic work place and equipment design and compliance with the 5R and the use of PPE are the most prioritized risk controls. The conclusion from this research is that the implementation of risk control in the form of ergonomic work place and equipment design, fulfilling the 5R and the use of PPE need to be done continuously to prevent accidents and occupational diseases.Keywords: Accident, diseases, HAZOP, control,Ã‚Â batik